A rare case of mixed germ cell tumor in a teenage girl: a case report - Vali, Faraz S.; Kyal, Amit; Chaudhary, Parul I.; Das, Sujatha; Mukherjee, Aprateem; Mukhopadhyay, Partha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Germ cell tumors represent only 20% to 25% of all benign and malignant ovarian neoplasms. Mixed germ cell tumors are a rare variety of non–dysgerminomatous germ cell tumors. They contain two or more elements; the most frequent combination being a dysgerminoma and an EST (Endodermal Sinus Tumor). We present a case of malignant mixed germ cell tumor comprising of yolk sac tumor, embryonal carcinoma and choriocarcinoma. A 13-year-old girl presented with a huge 25 x 18 cm mass in abdomen with raised values of CA-125, hCG, AFP (alpha-feto protein) and LDH (lactate dehydrogenase). She underwent laparotomy followed by unilateral salpingoopherectomy and infracolic omentectomy. Histopathology report revealed malignant mixed germ cell tumor comprising predominantly of EST with elements of embryonal carcinoma and non-gestational choriocarcinoma. Following surgery, she was started on adjuvant chemotherapy (Bleomycin, Etoposide and Cisplatin regimen). Mixed germ cell tumor (YST/EST, non-gestational choriocarcinoma and embryonal carcinoma) is a very rare tumor. Careful initial surgery with adequate staging biopsies followed by combination chemotherapy can greatly improve the prognosis of these patients